1997
DOI: 10.1111/j.1432-1033.1997.00518.x
|View full text |Cite
|
Sign up to set email alerts
|

Post‐Translational Activation of Non‐Homologous DNA End‐Joining in Xenopus Oocyte Extracts

Abstract: We have analysed the recircularisation of plasmid DNA, cut with two different endonucleases to generate non-homologous DNA ends, in extracts of unfertilised eggs and oocytes of Xenopus. We found that the capacity to join non-homologous DNA ends, generating diagnostic covalently closed monomer circles, appeared during oocyte maturation at the time of germinal vesicle breakdown. This enzyme function was post-translationally activated in oocyte extracts incubated with unfertilised egg extract containing active cd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…In order to directly investigate a requirement for the MRN complex in NHEJ, we used a plasmid-based NHEJ assay based on that of Aoufouchi et al (63) to determine NHEJ efficiency in X. laevis extract immunodepleted for XMre11 or XNbs1. The NHEJ substrate was produced by digesting pUC19 plasmid with PstI and SmaI generating a linear DNA with blunt and 3′-overhang ends.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to directly investigate a requirement for the MRN complex in NHEJ, we used a plasmid-based NHEJ assay based on that of Aoufouchi et al (63) to determine NHEJ efficiency in X. laevis extract immunodepleted for XMre11 or XNbs1. The NHEJ substrate was produced by digesting pUC19 plasmid with PstI and SmaI generating a linear DNA with blunt and 3′-overhang ends.…”
Section: Resultsmentioning
confidence: 99%
“…In order to investigate any requirement for the MRN complex in NHEJ in X. laevis , we initially conducted a plasmid-based NHEJ assay (63) using X. laevis egg extracts immunodepleted for XMre11 or XNbs1. Southern blot analysis of the end joining products indicated that NHEJ is unaffected in extracts lacking XMRN activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike the crude extract, this partially purified DNA ligase (PPL) could join ends with cohesive PSSs but not mismatched ends. When the Xenopus egg extract was passed through a Sephacryl S300 gel‐filtration column in 0.1 m KCl, a pool of fractions (> 66 kDa) was recovered that supported NHEJ between nonmatching ends ( Pst I‐ Sma I) with an activity essentially as efficient and precise as in the crude extract [17]. A more extensive effort to fractionate the Xenopus egg extract was recently reported [20].…”
Section: Cell‐free Nhej Systemsmentioning
confidence: 99%
“…Poly(ADP‐ribose)polymerase (PARP) is another enzyme that is activated by DNA strand breaks (single or double stranded), but PARP knock‐out mice are not hypersensitive to DNA damage, suggesting that it is not directly involved in the DNA repair process (reviewed in [58]). Nevertheless, NHEJ in a partially purified fraction from the Xenopus egg extract (‘fraction Y’), but not in the crude extract, was found to be inhibited in the presence of the PARP‐inhibitor 3‐aminobenzamide [17]. Both the joining of nonmatching and cohesive ends was affected.…”
Section: Pharmacological Inhibitorsmentioning
confidence: 99%